Profil Kemampuan Komunikasi Visual-Verbal Dalam Pemecahan Masalah Matematika - Silviana, Dewi; Hadi, Arnasari Merdekawati (Mandalika Mathematics and Educations Journal, 2019)
This research aim to discusses the profile of visual-verbal communication ability in mathematical problem solving from students' mathematics learning achievement. The instruments in this study were the researchers themselves, visual-verbal communication mathematics problem solving test and interview guidelines. Subjects in this study were 2 students with high learning achievement (PBT), 2 students with moderate learning achievement (PBS), and 2 students with low learning achievement (PBR). The results showed that students with high learning achievement improve verbal communication and mathematical communication skills that are more complicated than students with learning achievement who are solving mathematical problems. Meanwhile, students with low learning achievement solve problems by communicating verbal mathematical symbol.ÃƒÂ‚Ã‚Â AbstrakPenelitian ini bertujuan mengungkap profil kemampuan komunikasi visual-verbal dalam pemecahan masalah matematika dilihat dari prestasi belajar matematika siswa. Instrumen dalam penelitian ini adalah peneliti sendiri, tes pemecahan masalah matematika komunikasi visual-verbal dan pedoman wawancara. Subjek penelitian terdiri dari 2 orang siswa prestasi belajar tinggi (PBT), 2 orang siswa prestasi belajar sedang (PBS), dan 2 orang siswa prestasi belajar rendah (PBR). Hasil penelitian menunjukkan bahwa siswa dengan prestasi belajar tinggi meningkatkan kemampuan komunikasi visual dan matematis verbal yang lebih rumit dari siswa dengan prestasi belajar sedang memecahkan masalah matematika. Sementara, siswa dengan prestasi belajar rendah memecahkan masalah dengan komunikasi simbol matematis verbal. Siswa prestasi belajar rendah memecahkan masalah dengan komunikasi simbol matematis verbal.ÃƒÂ‚Ã‚Â